Expander processing and enzymes for a wheat-based diet for finishing pigs - Park, J.S.; Hines, Robert H.; Kennedy, G.A.; DeRouchey, Joel M.; Lee, D.J.; Maloney, C.A.; Cao, H; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Overall ADG and ADFI were not affected, but feed efficiency was improved with pelleting and further improvements resulted from expander processing. In a second experiment, enzyme supplementation to mash, but not pelleted, diets improved feed efficiency. Indeed, F/G for pigs fed mash with enzyme was similar to that for pigs fed pelleted diets.
Keywords: Swine; Expander; Wheat; Enzyme; Finishing pigs